SUMBER DAYA PANGAN BAHARI DALAM PERSPEKTIF SEJARAH - Sulistiyono, Singgih Tri (HUMANIKA, 2012)
We can track from history that Indonesian ancestors have long used maritime resources as food supply. They created many smart tools to catch fish and other edible creatures. Since colonial era up to now, the technology to exploit the sea is more and more modernized, from the gathering to preserving and packaging stage. Indonesian fishermen face challenges in competing with foreign fishermen on the matter of this kind of technology. Therefore it is important that the government keep on giving support and assistance and creating further innovations in order to manifest and secure its vision of self-sufficient country in the matter of food supply. Keywords: marime food resources